Immune Cell Infiltrate in Chronic-Active Antibody-Mediated Rejection - Sablik, Kasia A.; Jordanova, Ekaterina S.; Pocorni, Noelle; Clahsen-van Groningen, Marian C.; Betjes, Michiel G. H. (Frontiers in Immunology, 2020)
Background: Little is known about immune cell infiltrate type in the kidney allograft of patients with chronic-active antibody-mediated rejection (c-aABMR). Methods: In this study, multiplex immunofluorescent staining was performed on 20 cases of biopsy-proven c-aABMR. T-cell subsets (CD3, CD8, Foxp3, and granzyme B), macrophages (CD68 and CD163), B cells (CD20), and natural killer cells (CD57) were identified and counted in the glomeruli (cells/glomerulus) and the tubulointerstitial (TI) compartment [cells/high-power field (HPF)]. Results: In the glomerulus, T cells and macrophages were the dominant cell types with a mean of 5.5 CD3+ cells/glomerulus and 4 CD68+ cells/glomerulus. The majority of T cells was CD8+ (62%), and most macrophages were CD68+CD163+ (68%). The TI compartment showed a mean of 116 CD3+ cells/HPF, of which 54% were CD8+. Macrophage count was 21.5 cells/HPF with 39% CD68+CD163+. CD20+ cells were sporadically present in glomeruli, whereas B-cell aggregates in the TI compartment were frequently observed. Natural killer cells were rarely identified. Remarkably, increased numbers of CD3+FoxP3+ cells in the TI compartment were associated with decreased graft survival (p = 0.004). Conclusions: Renal allograft biopsies showing c-aABMR show a predominance of infiltrating CD8+ T cells, and increased numbers of interstitial FoxP3+ T cells are associated with inferior allograft survival.